Protective effects of Notoginsenoside R2 on reducing lipid accumulation and mitochondrial dysfunction in diabetic nephropathy through regulation of c-Src - Xieyi Guo; Liu Yang; Xiaoning An; Maofang Hu; Yilan Shen; Niansong Wang; Youhua Xu; Dingkun Gui (Chinese Medicine)
Abstract Background The treatment options to delay the progression of diabetic nephropathy (DN), a key contributor to chronic kidney disease (CKD), are urgently needed. Previous studies reported that traditional Chinese medicine Panax notoginseng (PNG) exerted beneficial effects on DN. However, the renoprotective effects of Notoginsenoside R2 (NR2), an active component of PNG, on DN have not been investigated. This study aimed to assess the therapeutic potential of NR2 in DN and explore its underlying mechanisms. Methods In vivo models were developed using db/db mice, while in vitro models utilized HK-2 cells exposed to high glucose and palmitic acid (HGPA). Online databases and Cytoscape software were employed to predict the potential targets of NR2. The expression of associated proteins was measured using immunohistochemistry and western blot. Lipid accumulation, oxidative stress levels, mitochondrial function and cell apoptosis were also assessed. Small interfering RNA was used in in vitro experiments to examine the effect of c-Src. Results NR2 ameliorated albuminuria, renal function and renal pathology in db/db mice. The activation of c-Src was suppressed in db/db mice and in HK-2 cells exposed to HGPA. NR2 inhibited JNK/STAT1 phosphorylation and CD36 overexpression. NR2 also ameliorated lipid accumulation, oxidative stress, mitochondrial dysfunction and cell apoptosis in vivo and in vitro. By inhibiting c-Src, HK-2 cells exposed to HGPA experienced less lipid deposition and mitochondrial damage, indicating the renoprotective effects of NR2 were correlated with the inhibition of c-Src. Conclusion NR2 ameliorated mitochondrial dysfunction and delayed the progression of DN partly through suppression of c-Src. The protective effects of NR2 might be related to a reduction in lipid accumulation. Graphical Abstract